DIFFERENCE IN THE NORDIC WALKING AND WALKING ON MORPHOLOGICAL CHARACTERISTICS OF WOMEN - Nebojša Čokorilo; Milena Mikalački; Darinka Korovljev; Goran Dimitrić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Walking is one of the few physical activities that suit most people: do not burden the body as intensely as other activities, injuries are rare, and it is necessary to determine the conditions for its exercise. Unlike normal walking, when the upper body is relatively passive, Nordic Walking activates more muscles of the back and arms. Using poles while walking reduces the load on the lower extremities, especially the hip joints, knees and ankles. Elderly people use sticks provides greater stability as it increases the support surface and thus reduces the risk of falls and injury, dangerous occurrence of fractures. The aim of the research is the evaluation of the effects of two models of walking and determine the differences in the results on the morphological characteristics of elderly women. The study comprised 87 individuals, females, aged between 50 and 60 years, territories, municipalities Novi Sad. In the first experimental group'' E1'' was regular and 30 females and their data are taken into consideration. The second experimental group'' E2'' had 27 trainees have been regular. Those in the control group were 30th The measurement of skin fold and circumference measurements and procedures were performed in accordance with IBP - player. The experimental program lasted three months. Differences between individual groups in each variable were calculated using LSD - post hoc test. Were found statistically significant differences between experimental groups and between the two experimental.